Clinical and functional outcome after restorative proctocolectomy. - de Silva, H; de Angelis, C; Soper, N; Kettlewell, MG; Mortensen, N; Jewell, D (1991)
Restorative proctocolectomy and ileal pouch-anal anastomosis (IPAA) has been carried out on 88 patients since 1982. Three different pouch designs (J, S and W) were used. Ten pouches had to be removed. Detailed analysis was performed on 61 patients (J = 23, S = 15, W = 23) whose pouches had been functioning for at least 6 months. There was no significant difference in surgical complications before or after ileostomy closure between pouch designs but the hospital stay was greater after construction of an S pouch (P less than 0.05). There were no significant differences in stool frequency, degree of continence or urgency between the three types. Twelve patients with J pouches required antidiarrhoeal medication compared with only one with S and five with W pouches. Only seven patients with S pouches could defaecate spontaneously compared with 22 with W pouches and all patients with J pouches (P less than 0.001). Twenty-five of 29 patients who had preservation of the anal transition zone had perfect continence compared with 23 of 32 with a mucosal proctectomy (P = n.s.). Pouchitis occurred in 13 patients, all of whom had ulcerative colitis. In a subgroup of 23 patients, pouch evacuation was assessed scintigraphically. There was no difference in pouch capacity or total volume evacuated, but spontaneous evacuation was better in J and W pouches compared with S pouches.